Hubungan Lingkar Perut dan Pola Makan dengan Kadar Gula Darah Pada Penderita Diabetes Melitus Usia Dewasa Di Wilayah Kerja UPTD Puskesmas Pasar Ikan Kota Bengkulu Tahun 2024 - Wulandari, Melsa Putri; Suryani, Desri; Yulianti, Risda (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Diabetes mellitus is a metabolic disease with symptoms of hyperglycemia caused by abnormalities in insulin secretion, insulin action, or both. Central obesity is caused by excessive fat deposits in the abdomen. Excessive fat accumulation results in insulin resistance, which is one of the factors in increasing blood glucose levels in diabetes mellitus sufferers. Diet is very influential in controlling blood sugar levels in the body to avoid complications due to diabetes mellitus. The aim is to determine the relationship between abdominal circumference and eating patterns with blood sugar levels in adult diabetes mellitus sufferers. The design used in this research was analytical observational using a cross-sectional approach, the total number of respondents was 76 people, with purposive sampling technique. The data taken is central obesity data by measuring abdominal circumference directly using a Mettline measuring tape and eating patterns using the Percieved Dietary Adherence Questionnaire (PDAQ) form. Statistical analysis uses the Chi-square test to determine the relationship between the independent variable and the dependent variable. The research results showed that 82.9% of respondents had central obesity and 52.6% of respondents had a diet that did not comply with dietary recommendations for diabetes mellitus sufferers. Based on statistical tests using chi square, it shows that there is a relationship between abdominal circumference and blood sugar levels in diabetes mellitus sufferers (p value = 0.019) and eating patterns and blood sugar levels in diabetes mellitus sufferers (p value = 0.006). The conclusion of this research is that there is a relationship between abdominal circumference and diet and blood sugar levels in adult diabetes mellitus sufferers in the UPTD area of the Puskesmas Pasar Ikan, Bengkulu City in 2024.